Reference intervals of embryos/fetuses heart rate between 6 and 14 weeks of pregnancy. (September 2014) - Araujo Júnior, Edward; Costa, Raquel Silva; Fonseca, Bruna Custódio; Martins, Wellington P.; Pires, Claudio Rodrigues; Zanforlin Filho, Sebastião Marques
Abstract Objective: To determine reference intervals for the embryos/fetuses heart rate (HR) between 6 and 14 weeks of pregnancy. Methods: A retrospective cross-sectional study was carried in a single center with singleton pregnancies of embryos/fetuses with a crown-rump length (CRL) between 5 and 85 mm. The HR was assessed by real time M-mode or spectrum Doppler ultrasound. To evaluate the correlation between embryo/fetal HR and CRL, polynomial equations were calculated, with adjustment by the determination coefficient (R2). Results: A total of 5867 pregnancies were assessed. The mean gestational age was 10.37 ± 2.12 weeks. The mean maternal age was 26.41 ± 6.78 years. The mean embryo/fetal HR (bpm) for the CRL (mm) intervals 5├15; 15├25; 25├35; 35├45; 45├55; 55├65; 65├75; 75├85 was 145.1 ± 18.7; 167.2 ± 10.1; 166.9 ± 8.7; 165.5 ± 6.9; 162.2 ± 6.8; 159.2 ± 6.4; 157.1 ± 6.4; 154.9 ± 7.3; respectively. The following third-order equation best represented the correlation between embryo/fetal HR and CRL: HR = 119.25 + 3.596*CRL-0.07954*CRL2 + 0.00051*CRL3 (R2 = 0.36). Conclusion: Reference intervals of HR in embryos/fetuses in a large sample were determined. These reference intervals can be used in high-risk early pregnancy losses.